THE STRATEGY IMPLEMENTED BY PT BANK RAKYAT INDONESIA (PERSERO) PATTIMURA SEMARANG BRANCH TO ANTICIPATE FRAUD RELATED TO LETTER OF CREDIT (L/C) - Mukofidhotun - Umaroh; Paniya - Paniya (Politeknik Negeri Semarang, 2013)
This article is a study of the Strategy Implemented by PT Bank Rakyat Indonesia (Persero) Pattimura Semarang Branch to Anticipate Fraud Related to Letter of Credit. The data used in this article are obtained through an interview with letter of Credit (L/C) department staff of PT Bank Rakyat Indonesia (Persero) Pattimura Semarang Branch. The interviews were held 6 (six) times and each interview took two hours. As a paying or negotiating bank commonly honors drafts or makes payment to beneficiary (exporter) based only on documents, the bank may bear risks of financial loss. The potential financial loss by a bank is due to the custom and practice of documentary credit among the parties involved in an L/C transaction, which are based on documents, not on goods. A bank commonly honors draft presented by a beneficiary since the required documents presented to the bank are in compliance with terms and conditions stipulated in the L/C to prevent potential financial loss, the bank applies a certain strategy of carefulness.